PENGARUH PEMASARAN RELASIONAL TERHADAP KEPUASAN DAN LOYALITAS PELANGGAN (STUDI PADA TOKO RAJA AGUNG OUTLET BEKASI) - Bainaturrahma, Nafa; Savitri Noor, Laili (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2025)
This study aims to analyze the influence of relationship marketing on customer satisfaction and loyalty, with satisfaction as a mediating variable at Raja Agung Outlet Bekasi. The research uses a quantitative approach with a survey method by distributing questionnaires to 100 respondents who are customers of Raja Agung. The sampling technique used is purposive sampling. Data processing and analysis were carried out using SmartPLS 3.2 software. The results show that relationship marketing has a positive and significant effect on both customer satisfaction and loyalty. Moreover, customer satisfaction also positively affects loyalty and is able to mediate the influence of relationship marketing on loyalty. These findings highlight the importance of relationship marketing strategies in increasing customer loyalty through perceived satisfaction.